Economic Burden and Influencing Factors of Acute Gastroenteritis in China: A Population-Based Face to Face Survey in 2018 - Huo, Yue; Gao, Fei; Wang, Jiayu; Liu, Zhongwei; Zhou, Liangru; Gu, Baiyang; Zhang, Xin; Ma, Yi (Frontiers in Public Health, 2022)
Background: Acute gastroenteritis is an important and common public health problem worldwide, whose occurrence is primarily due to ingestion of contaminated unclean food. The purpose of this study was to estimate the food triggers of the onset of acute gastroenteritis, the places of exposure, as well as the economic burden of the disease due to the illness. Methods: A multi-stage stratified random sampling method was used for the questionnaire study, and 19,647 questionnaires were distributed at home, including 696 patients with acute gastroenteritis. Information on economic burden, foodborne exposure elements, and disease treatment was investigated. One-way variance and multiple stepwise regression analysis were used to investigate the factors associated with the economic burden of acute gastroenteritis. Quantification risk analysis and sensitivity analysis were performed to estimate the uncertainty and risk factors of the economic burden of acute gastroenteritis. Results: The total economic burden of patients with acute gastroenteritis was 63969.22 CNY (Chinese Yuan), of which the direct economic burden accounted for 63.82%; the annual per capita economic burden was 131.35 CNY. The economic burden of illness from ingestion of vegetable products and exposure at home was high. Age, region, disease duration, and disease treatment were the main factors significantly associated with the economic burden of acute gastroenteritis (P < 0.05). The average economic burden of patients with acute gastroenteritis was approximately 571.84 CNY/person (95% CI: 227–1459). Sensitivity analysis showed that the greatest impact was from the indirect economic burden. Conclusions: Acute gastroenteritis disease, for which foodborne exposure is the main suspected cause, imposes an economic burden on patients. It is necessary to continuously strengthen the construction of foodborne disease surveillance networks, intensify the supervision of key foods, and educate the population to reduce the occurrence of diseases.